The Role of Experiential Learning in Transforming Music Appreciation Education and Pedagogical Practices - Jiang, Min (Pacific International Journal, 2024)
This study examines the role of experiential learning in transforming high school music appreciation education. Grounded in the experiential learning theories of John Dewey, Kurt Lewin, and Jean Piaget, the research explores how active and immersive approaches can enhance students' emotional and intellectual engagement with music. Utilizing a mixed-methods approach, the study incorporates teacher interviews, student surveys, and a case study centered on a specific music lesson (Homesickness Melody). Results indicate that experiential learning fosters creativity, deeper emotional connections, and critical thinking skills, while addressing some of the limitations of traditional music teaching methods. However, challenges such as teacher readiness, resource availability, and student participation were identified as key barriers to implementation. The case study demonstrated the effectiveness of kinesthetic and sensory activities in enhancing students' appreciation of music. Overall, the findings suggest that experiential learning offers a promising pedagogical strategy for music education, promoting both aesthetic literacy and emotional engagement.